The Long-Run Effect of Migration on Firms' Trade: Evidence from China - Baiardi, Anna; Ammon, Christina (Economic Development and Cultural Change, 2025)
We empirically assess the long-term effect of migration on the exporting behavior of firms in the migrants' origin country. We focus on ethnic migrant networks formed as a result of a mass migration wave of ethnic Cantonese people from the Chinese provinc
Keywords: Migration on exports; Migration on Firms; Trade; China